Medication Prescribing Practices in Croatian Dental Offices and Their Contribution to National Consumption - Ivana Šutej; Dragan Lepur; Darko Božić; Katja Pernarić (Elsevier, 2021)
Objectives: The objective of this study was to analyse the pattern of medication prescribing among dental practitioners in the Republic of Croatia and to compare it with general medical practice patterns at the national level. Methods: Data on drug prescriptions were obtained from the Croatian Health Insurance Fund. The number of dentist prescriptions, the cost of medicine denominated in the national currency (Croatian Kuna [HRK]), and the number of packages and days prescribed have been included in the analysis. Results: Results indicate that there was an increase in medication prescribing(+5.7%) by dentists, with antimicrobials comprising the majority, whereas national medical antimicrobial prescribing had slightly decreased. Antibiotics accounted for 80% of all dentists' prescriptions, with penicillins being the most commonly prescribed. In particular, amoxicillin with clavulanic acid accounted for 56.4% of all antibiotics prescribed. Such broad-spectrum antibiotics were prescribed more frequently than those of narrow-spectrum. Antibiotics were followed by nonsteroidal anti-inflammatory drugs, with prescribing frequency for ibuprofen increasing by 75%. Conclusion: Current trends show an increase in the overall prescription rate for all medications prescribed by dentists. The largest increase was observed for the broad-spectrum amoxicillin with clavulanic acid, and ibuprofen. As the apparent widespread use of broad-spectrum antibiotics by dentists in Croatia is in contrast to national and international recommendations for antibiotic stewardship, there is a need for further prospective investigation and possible provider education and guidelines.